Integration of Activity Specification into DEVS Modeling & Simulation Development Environment - Alshareef, Abdurrahman; Zeigler, Bernard P. (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2020: Anais do II Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2020.12494, 2020)
We propose an integrative environment for the modeling and simulation of activity specification. The devised approach relies on the DEVS (Discrete Event System Specification) formalism for the foundational semantics of the essential activity elements. The code generation takes place afterward, targeting specific DEVS-compliant modeling and simulation (M&S) environments such as DEVS-Suite and MS4 Me. The modelers can set parameters or modify the code to satisfy specific needs. The simulation can then be conducted with behavior monitoring and visualization. We demonstrate the approach with observations about performance evaluation and tracking. Such environments have the potential to facilitate computational model development for System of Systems via full-scale simulation support.